2014
DOI: 10.1097/mnm.0000000000000187
|View full text |Cite
|
Sign up to set email alerts
|

Clinical validation of high-resolution image reconstruction algorithms in brain 18F-FDG-PET

Abstract: We have demonstrated that a high-resolution image reconstruction algorithm for brain F-FDG-PET is promising without the use of a GF because of high true coincidence counts and that combined with PSF and TOF is optimal for obtaining a better SNR of the image.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…Previous studies have clarified that the combined use of PSF and TOF leads to greater improvements in SNR, spatial resolution, and uniformity than using PSF or TOF alone [21]. Similar results have been observed in brain PET imaging studies [22,23]. PSF + TOF has also been observed to increase SUVs for lesions, exerting a particularly large effect on small structures [24,25].…”
Section: Shao Et Al Investigated the Effects Of Psf Correction On Bra...supporting
confidence: 64%
“…Previous studies have clarified that the combined use of PSF and TOF leads to greater improvements in SNR, spatial resolution, and uniformity than using PSF or TOF alone [21]. Similar results have been observed in brain PET imaging studies [22,23]. PSF + TOF has also been observed to increase SUVs for lesions, exerting a particularly large effect on small structures [24,25].…”
Section: Shao Et Al Investigated the Effects Of Psf Correction On Bra...supporting
confidence: 64%
“…under pharmacological or non-pharmacological experimental challenges, are expected to advance molecular characterization of neurodegenerative disorders and CVD in clinical human neurosciences. Finally, improvements in PET imaging temporal resolution have opened a field for integrating time-of-flight 33 , 34 information into the reconstruction process, leading to the high resolution of today's PET/CT systems, again, improving imaging capabilities, potentially reducing acquisition times and improving the specificity of the imaging set-up.…”
Section: Resultsmentioning
confidence: 99%
“…However, that study did not find a benefit of TOF with an SiPM-PET system for brain PET. Nagaki et al found that contrast in [ 18 F]FDG brain imaging was not improved using the PMT-PET system at a timing resolution of 555 ps [30]. The sensitivity gain using TOF was increased as a function of increasing the object size [31].…”
Section: Discussionmentioning
confidence: 99%